Parametric Model Study for Outdoor Routers Cost Estimation - Abel Yu Hao, Chai; Chean Hung, Lai; Hieng Tiong, Su; Natalie, Lim; Chamath Kanalaka, Vithanawasam; Yi Lung, Then; Fei Siang, Tay; Lisa, Yong (2020)
Rural internet connectivity is a challenging issue among the Internet Service Providers (ISPs) because of high cost and risk associated with unforeseen circumstances. Rural Internet implementations often relate to outdoor equipment such as routers, antennas and access points. Outdoor routers seem to be the main concern since some routers are built in with internal antennas and access points functionality. This paper aims to develop a parametric model for estimating outdoor router cost. The model can provide more practical and accurate cost estimation for ISPs. The model uses Friis Transmission Equation with parameters obtained from datasheets. The key parameters are selected by using P-value regression analysis. The parametric model with original key parameters and unique key parameters have better performance and can provide more realistic cost estimation.